Molecular mobility and activity in an intravital imaging setting - implications for cancer progression and targeting - Nobis, Max; Warren, Sean C; Lucas, Morghan C; Murphy, Kendelle J; Herrmann, David; Timpson, Paul (Journal of cell science, 2018)
Molecular mobility, localisation and spatiotemporal activity are at the core of cell biological processes and deregulation of these dynamic events can underpin disease development and progression. Recent advances in intravital imaging techniques in mice are providing new avenues to study real-time molecular behaviour in intact tissues within a live organism and to gain exciting insights into the intricate regulation of live cell biology at the microscale level. The monitoring of fluorescently labelled proteins and agents can be combined with autofluorescent properties of the microenvironment to provide a comprehensive snapshot of cell biology. In this Review, we summarise recent intravital microscopy approaches in mice, in processes ranging from normal development and homeostasis to disease progression and treatment in cancer, where we emphasise the utility of intravital imaging to observe dynamic and transient events We also highlight the recent integration of advanced subcellular imaging techniques into the intravital imaging pipeline, which can provide in-depth biological information beyond the single-cell level. We conclude with an outlook of ongoing developments in intravital microscopy towards imaging in humans, as well as provide an overview of the challenges the intravital imaging community currently faces and outline potential ways for overcoming these hurdles.